Long live the cat: Ocelot population viability in a planned reintroduced population in Texas, USA - Lindsay A. Martinez; Jason V. Lombardi; Israel D. Parker; Forrest East; Tyler A. Campbell; Roel R. Lopez (Ecosphere)
Abstract Reintroductions are often needed to recover carnivore populations and restore ecological processes. Felids are common subjects of reintroduction efforts, but published population models informing felid reintroduction plans are uncommon, and poor planning has sometimes caused issues in felid reintroduction programs. In the United States, ocelots (Leopardus pardalis pardalis) are classified as endangered, and recovery requires population expansion into historic habitat. A multi‐organization effort is underway to establish a new ocelot population in Texas by releasing ocelots into an area of 478 km2 of suitable habitat in ocelots' historic but now unoccupied range. In this study, we used population viability analyses to compare different ocelot reintroduction strategies for the identified reintroduction area. Based on a potential ocelot breeding program's limitations, we modeled reintroduction using a founding population of no more than six ocelots and no more than four ocelots released per year for no more than 15 subsequent years. Within these limitations, we assessed projected population abundances and extinction risks after 30 years for 20 different reintroduction strategies. We found that long‐term releases are necessary to establish a viable population; under conservative model assumptions, releasing six ocelots in the initial year and then releasing four individuals annually for an additional 10–15 years is necessary for attaining a projected population greater than 36.62 ocelots (baseline) with <6% extinction risk. We also found that ocelot population abundance is about equally sensitive to post‐release mortality and inbreeding depression. This highlights the importance of not only supporting reintroduced ocelots' survival but also managing for high genetic diversity in the reintroduction program. Further, we found that realistic but more liberal assumptions on the carrying capacity of the reintroduction area and the age of first reproduction for ocelots increase projected population abundances (53.95 individuals and 61.26 individuals, respectively), and thus reintroduction success. The model's sensitivity to carrying capacity suggests that long‐term habitat protection and expansion are among the most important management actions to support ocelot reintroduction. Our study establishes the first population viability model for an ocelot reintroduction plan anywhere across the species' wide geographic range, and it reinforces several key considerations for wildlife reintroduction efforts worldwide.